Naseljevanje in prostorski razvoj slovenskih naselbin v Pueblu v Koloradu - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Settling and spatial development of Slovene settlements in the city of Pueblo, Colorado. Pueblo in southern Colorado represents one of the many cities in American West which owes its development to the development of railroads and roads and industries. Fast development of industry, especially after 1880 caused mass immigration, especially from Italy and Austria- Hungary. Number of inhabitants of Pueblo grew fast, from 3,217 in 1880 to 45,444 in 1910. The percentage of foreign born and their children in the city grew to 41.13% in 1910. According to the U.S. census data of 1910 there lived in Pueblo approximately 2,400 immigrants and their children with Slovene mother tongue. Most of them were from Dolenjska, Bela krajina and Notranjska. They settled in southeastern part of the city, in Grove and Bessemer in the Ward 6. They represented in the Precinct 2 more then half of all population, in Precinct 3 more than one quarter of all population. In the beginning of the 20th century in Pueblo the largest Slovene settlement in the U.S. West developed. Slovenes are still present in Pueblo today. Americans and older immigrants called Slovene immigrants Bojons . In the beginning of the 20th century it meant an offensive word; in the beginning of the 21st century it is used as a compliment when the others in Pueblo with this word describe inhabitants of Slovene ancestry as well as the other people from South Slavic lands.
Keywords: United States of America; ZDA; slovenski izseljenci; popis prebivalstva; etnična struktura; Bojoni; Pueblo; Colorado; Kolorado